EVALUASI KIMIA FISIKA DAN UJI STABILITAS SEDIAAN COLD CREAM YANG MENGANDUNG EKSTRAK ETANOL DAUN CIPLUKAN (Physalis angulata L.) DENGAN 3 JENIS MINYAK Olive, Caprylic Dan Parafin - Habibie Deswilyaz Ghiffari; Delladari Mayefis; Ayu Amelia; Gina Fernanda (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2025)
Physalis angulata L. (ciplukan) is an annual plant with potential medicinal properties, including pain relief. This study aims to formulate a cold cream containing ciplukan leaf extract and evaluate its physical stability. The leaf extract was obtained by maceration using 96% ethanol and concentrated using a rotary evaporator. Cold cream formulations were prepared with extract concentrations of 0%, 5%, and 10%, utilizing three types of oils (olive, caprylic, and paraffin). Evaluations included organoleptic properties, pH, homogeneity, adhesion, spreadability, viscosity, cream type, and stability, analyzed using One-Way ANOVA. Results showed that all formulations exhibited good physical properties and were classified as oil-in-water (O/W) type creams. pH values ranged from 4 to 6, adhesion times from 1.19 to 4.94 seconds, and spreadability from 4.52 to 5.16 cm, with no significant differences among extract concentrations or oil types (p > 0.05). Increasing the extract concentration from 5% to 10% resulted in a slight decrease in pH, which remained within the safe range, maintained homogeneity, slightly reduced spreadability, and improved physical stability, especially at 10%. The formulation containing 10% ciplukan leaf extract showed the best stability and was well accepted as a cold cream preparation.